Flexibility in Aquatic Food Web Interactions: Linking Scales and Approaches - Ellen van Velzen; Sabine Wollrab; Onur Kerimoglu; Ursula Gaedke; Hans-Peter Grossart; Minoru Kasada; Helena C. L. Klip; Stefanie Moorthi; Tom Shatwell; Patch Thongthaisong; A. E. Friederike Prowe (Ecosystems, 2025)
Trophic interactions determine food web structure and influence biodiversity, community structure, ecosystem functioning, and food web responses to global change. These interactions are highly flexible, changing on temporal scales from diurnal to evolutionary times due to phenotypic plasticity, rapid evolution and species sorting. Small-scale experimental and theoretical studies of plankton interactions have demonstrated a high relevance of this flexibility for community dynamics and ecosystem processes in small, simplified communities. However, the extent to which this flexibility affects larger-scale systems, for example, global ocean dynamics and their responses to global change, is still poorly understood. Differences in methodology, focus and terminology between research disciplines limit our ability to project established effects of flexible trophic interactions onto larger spatial and temporal scales. We propose to bridge this gap with a general framework for upscaling knowledge from small-scale research to large-scale models. Building on examples from plankton communities, we use this framework to show how mechanisms demonstrated in small-scale studies can be linked to ecosystem functions relevant at large scales. We argue for incorporating flexibility in large-scale process-based models to improve their realism and predictive power, and discuss challenges and ways forward for achieving this. Finally, we suggest several concrete ways for upscaling small-scale studies to make their findings more relevant for large-scale research, to close existing knowledge gaps and to improve our understanding of how flexible trophic interactions affect dynamics and processes across scales.

The relationship between total organic carbon and bottom water redox state in North American black shales - Samantha R. Ritzer; Shane Schoepfer; Bella Bussian; Una C. Farrell; Tiffani Fraser; Charles M. Henderson; Junyao Kang; Chiza N. Mwinde; Austin Patch; Erik A. Sperling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Neurophysiological mechanisms underlying sex- and maturation-related variation in pheromone responses in honey bees (Apis mellifera) - Gabriel Villar; Thomas C. Baker; Harland M. Patch; Christina M. Grozinger (Journal of Comparative Physiology A, 2015)

Effect of Chromated Copper Arsenate Structures on Adjacent Soil Arsenic Concentrations - Steven C. Patch; Katherine Scheip; Billy Brooks (Bulletin of Environmental Contamination and Toxicology, 2011)

Malaria severity and human nitric oxide synthase type 2 (NOS2) promoter haplotypes - Marc C. Levesque; Maurine R. Hobbs; Charles W. O’Loughlin; Jennifer A. Chancellor; Youwei Chen; Ariana N. Tkachuk; Jennifer Booth; Kistie B. Patch; Sallie Allgood; Ann R. Pole; Carolyn A. Fernandez; Esther D. Mwaikambo; et al. (Human Genetics, 2010)

Lead Content and Exposure from Children’s and Adult’s Jewelry Products - R. P. Maas; S. C. Patch; T. J. Pandolfo; J. L. Druhan; N. F. Gandy (Bulletin of Environmental Contamination and Toxicology, 2005)

Inhalation and Ingestion of Phthalate Compounds from Use of Synthetic Modeling Clays - R. P. Maas; S. C. Patch; T. J. Pandolfo (Bulletin of Environmental Contamination and Toxicology, 2004)